Study of the Antioxidant and Anti-Inflammatory Properties of the Biological Extracts of Psophocarpus tetragonolobus Using Two Extraction Methods - Hussein Bassal; Akram Hijazi; Hussein Farhan; Christine Trabolsi; Bouchra Sayed Ahmad; Alia Khalil; Marc Maresca; Fawaz El Omar (Molecules, 2021)
Psophocarpus tetragonolobus has long been used in traditional medicine and cuisine. In this study, Psophocarpus tetragonolobus extracts were isolated by maceration and ultrasound-assisted extraction and were evaluated for their antioxidant and anti-inflammatory effects in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. The obtained results show that both extracts (maceration and ultrasound) were rich in bioactive molecules and exerted substantial antioxidant and anti-inflammatory effects. The P. tetragonolobus extracts’ treatment in LPS-stimulated RAW264.7 macrophages resulted in a significant downregulation of the expressions of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and IL-1β mRNA. In addition, the P. tetragonolobus extracts’ treatment attenuated inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) protein expression. Our observations indicate that there is no significant difference between the two studied extracts of P. tetragonolobus in terms of biological properties (specifically, antioxidant and anti-inflammatory effects. Regardless of the extraction method, P. tetragonolobus could be used for treating diseases related to oxidative stress and inflammatory reactions.